2009
DOI: 10.1111/j.1462-5822.2008.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the expression and adhesin function of H7 flagella in the interaction ofEscherichia coliO157 : H7 with bovine intestinal epithelium

Abstract: SummaryEnterohaemorrhagic Escherichia coli O157 : H7 is a bacterial pathogen that can cause haemorrhagic colitis and haemolytic uremic syndrome. In the primary reservoir host, cattle, the terminal rectum is the principal site of E. coli O157 colonization. In this study, bovine terminal rectal primary epithelial cells were used to examine the role of H7 flagella in epithelial adherence. Binding of a fliCH7 mutant O157 strain to rectal epithelium was significantly reduced as was binding of the flagellated wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 81 publications
6
118
0
Order By: Relevance
“…This transition can be associated with a change in cellular phenotype. For instance, when motile bacteria, such as Escherichia coli, adhere to a substratum (33,82,83), motility ceases, cell multiplication continues (84)(85)(86)(87), and early biofilm-related genes are upregulated, including those that encode additional adhesins (88)(89)(90). Although Karatan and Watnick (91) suggested that bacteria at this point can form either an adherent monolayer biofilm or a multilayer biofilm, the former is not sufficient to encompass some of the main characteristics of a complex biofilm, most notably the formation of ECM and a three-dimensional, controlled microenvironment that facilitates biofilm growth, nutrient acquisition, control of gas and pH, and cell-cell signaling (92)(93)(94)(95)(96)(97).…”
Section: Defining a C Albicans Biofilm: Lessons From Bacteriamentioning
confidence: 99%
“…This transition can be associated with a change in cellular phenotype. For instance, when motile bacteria, such as Escherichia coli, adhere to a substratum (33,82,83), motility ceases, cell multiplication continues (84)(85)(86)(87), and early biofilm-related genes are upregulated, including those that encode additional adhesins (88)(89)(90). Although Karatan and Watnick (91) suggested that bacteria at this point can form either an adherent monolayer biofilm or a multilayer biofilm, the former is not sufficient to encompass some of the main characteristics of a complex biofilm, most notably the formation of ECM and a three-dimensional, controlled microenvironment that facilitates biofilm growth, nutrient acquisition, control of gas and pH, and cell-cell signaling (92)(93)(94)(95)(96)(97).…”
Section: Defining a C Albicans Biofilm: Lessons From Bacteriamentioning
confidence: 99%
“…Short-chain fatty acids are found in concentrations ranging from 20 to 140 mM in the large bowel, and recognition of this signal, along with the AI-3 and interkingdom signaling molecules, likely contributes to EHEC niche recognition and adaptation. Some evidence also suggests that the flagellum acts as an initial adhesin to epithelial cells from the bovine terminal rectum (25).…”
Section: Motilitymentioning
confidence: 99%
“…Flagella and motility enhance encounter rates of pathogenic bacteria with host cells or tissues, thus facilitating the spread of infection, and therefore flagellation is advantageous to pathogenic bacteria at the early stages of infection (Ottemann & Miller, 1997;Ramos et al, 2004). In addition, the flagellar filament can act as an adhesin, and thereby increases the frequency and intimacy of early host-pathogen interactions Giró n et al, 2002;Mahajan et al, 2009;Roy et al, 2009). On the other hand, flagella are highly immunostimulatory in the host and recognized by innate immunity defences (Hayashi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For newborn meningitis-associated E. coli (NMEC), which represents another extraintestinal E. coli pathogroup, the flagellar structure rather than the motility function has been shown to be relevant for bacterial association with and invasion into human brain microvascular endothelial cells (Parthasarathy et al, 2007). Similarly, flagella of diarrhoeagenic E. coli have been demonstrated to be directly involved in the adherence to epithelial cells (Giró n et al, 2002;Mahajan et al, 2009;Roy et al, 2009) and mucins , and also to contribute to host cell invasion (Luck et al, 2006). Thus, flagellation contributes to the pathogenicity of E. coli through motility and adhesive-or invasion-promoting properties.…”
Section: Introductionmentioning
confidence: 99%